(untitled) (Journal of the College of Basic Education, 2025)
This research aims to explain the reasons, methods, causes, pillars and conditions that allow some of the legal rulings to be suspended after the era of the Prophet, or some of them to be legislated after they were prohibited during the era of the Prophet. If these rulings had not been suspended or legislated, people would have been in difficulty and hardship, or they would have been in dire need, or their interests would have been lost, or their way of life would have been disrupted. The research also aims to uncover the theory that studies these cases, methods and events. These were the objectives of this modest research. Among its most prominent results were: First: The theory has a pioneering presence in the books of Islamic jurisprudence and the principles of jurisprudence in terms of the occurrence of jurisprudential examples, whether the example was a suspension of rulings or a legislation for them after they were originally prohibited during the era of the Prophet, and in all chapters of Islamic jurisprudence. Second: The suspension of rulings does not mean their nullification or cancellation, as the suspension includes the possibility of applying the ruling again in other eras or times, given the availability of the pillars and conditions, their absence, or for other reasons. Nullification, suspension, or cancellation is the final suspension of the ruling for as long as the world exists. Third: The mujtahid is a legislator in terms of his inheritance from the Prophet (peace and blessings of Allah be upon him and his family and companions) in explaining the rulings and applying them in the correct application intended by Allah, the Almighty. The contemporary mujtahid, with this inheritance, is obligated to apply the method of the Prophet and the method of the Companions in suspending or legislating the ruling, which is his personal duty. Rather, it is one of his qualities that the people of knowledge have defined for him, that he should have extensive knowledge of the principles and methods of deduction, and if he shirks it, he will be sinful. The contemporary mujtahid will be rewarded, God willing, for applying these methods. If he is correct, he will have two rewards, and if he is wrong, he will have one reward. The mujtahid is not, by doing so, being bold with the rulings of God, as some may think, who are not understanding and knowledgeable enough to know the method of the Prophet (peace and blessings of God be upon him and his family and companions) and the Companions in deriving rulings. Fourth: The Companions and the Followers (may God be pleased with them) practiced suspending or legislating the legal rulings after they were prohibited during the era of the Prophet, with the utmost scientific methodology and jurisprudential reasoning, the most important of which was: suspending the ruling or legislating it due to (the absence of the pillars or conditions, the most important of which are: the disappearance of the place, the corruption of the time, disregard for the legal rulings, so they are suspended, or disregard for the rulings that were originally prohibited, so they are legislated, or arbitrariness. Fifth: The suspension of Shari’a rulings or their legislation after they were prohibited during the era of the Prophet can be explained by more than one explanation, according to what some jurists explained and what others explained. The legislation of (a specific ruling) may be explained by some due to the corruption of the times, and others due to the people’s need... and so on, as mentioned in the folds of this research regarding (the ruling on pricing). Sixth: The theory does not contain any boldness regarding the rulings of God and His Messenger, as some who do not understand the approach of the Prophet (peace and blessings of God be upon him and his family and companions) and the noble companions with a sound and correct understanding may imagine. We seek refuge in God from this prophetic approach and the approach of the companions, which the theory addressed with clarification and explanation, being described as bold. Rather, the theory is an expression of the revelation of an actual application of the approach of the Prophet (peace and blessings of God be upon him and his family and companions) in his legislation and suspension of many Shari’a rulings, such as his legislation of salam or advance sales after he had prohibited such sales due to the people’s need for salam or advance sales. The theory It is a practical application of the methods of the Companions (may Allah be pleased with them) that they understood and learned from him (peace and blessings of Allah be upon him and his family and companions) by including our Master Imam Ali (may Allah be pleased with him) in the liability of craftsmen after they were not liable for the damaged manufactured items they owned during the time of the Prophet (peace and blessings of Allah be upon him and his family and companions), and the Companion Omar bin Al-Khattab (may Allah be pleased with him) suspending the prescribed punishments in the Year of the Ashes, which was a year of famine and drought. Can this suspension or legislation of the rulings issued by the Prophet (peace and blessings of Allah be upon him and his family and companions) be considered an affront to Allah Almighty, or could this suspension or legislation issued by the Companions (may Allah be pleased with them) be an affront to Allah Almighty and His Messenger? Seventh: This theory includes other jurisprudential theories such as the theory of (the loss of the place) and the theory of (the abuse of rights), and it includes jurisprudential rules such as the rule of (the change of rulings cannot be denied with the change of times), and it includes an important source of legislation, which is (interest(.